Robert Louis Stevenson - Robert Louis Stevenson; Robert Louis Stevenson (New Delhi Rising Sun, 2005)
David Balfour survives a murder attempt by his uncle, Ebenezer, who sends him up a dangerous, dark tower staircase during a storm. David confronts his uncle about the betrayal and discovers evidence that his father was the elder brother, making David the true heir to the Shaws estate.
Keywords: escalating danger while staying with his miserly and treacherous Uncle Ebenezer; developing, understanding of the novel$1 (Bs themess